Implementasi Gugatan Perwakilan Kelompok (Class Action) pada Sistem Peradilan di Indonesia - Marbun, Marliana Boru (UNIVERSITAS SERAMBI MEKKAH, 2025)
Class action lawsuits have been introduced as a mechanism to provide access to justice for groups of people who have suffered losses due to unlawful actions. The mechanism involves a group of individuals with similar interests collectively suing or being sued by another party, with a designated representative acting on behalf of the entire group. Although regulated by several laws such as the Consumer Protection Law and the Environmental Management Law, its practice still faces challenges, particularly due to the lack of clarity in the procedures within Indonesian civil procedural law. This research employs a normative juridical approach and gathers primary and secondary data through literature studies. Supreme Court Regulation No. 1 of 2002 provides guidelines for the courts. However, many lawsuits are rejected on the grounds of being inadmissible due to the invalidity of the class action suit. This study aims to analyze the effectiveness of class action implementation and provide recommendations for improving the legal system to be more responsive to community needs.